ALIGNMENT SYSTEMS AND PASSIVE-ANTIPASSIVE DISTRIBUTION IN NILOTIC LANGUAGES (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper discusses the occurrence of passive and antipassiveconstructions in Nilotic languages in relation to the question of whetherNilotic languages developed from an ergative-absolutive to a nominativeaccusative case marking system or vice versa. This is a question based onDixon’s (1994) claim that the re-interpretation of the passive can change alanguage from a nominative-accusative to an ergative-absolutive status(see pp. 187-192), or that the re-interpretation of the antipassive can altera language from an ergative-absolutive to a nominative-accusative status(see pp. 193-203). To address the question, the paper uses data fromWestern, Southern, and Eastern Nilotic languages. The data show thatNilotic languages display mixed-alignment systems and that thedistribution of passive and antipassive constructions does not provide anyconclusive answer about the origin of Nilotic languages. However, based onthe observation that Southern Nilotic languages have a marked-nominativealignment system, which is a hybrid between ergative-absolutive andnominative-accusative systems, and that some of the languages illustratedwith display residues of ergativity (in particular, the mixed Sa-So alignmentin passive constructions in Southern Nilotic), the paper comes to thetentative conclusion that Nilotic has an ergative-absolutive origin.